Smart Water Level Indicator - Ismail, Ammar Asyraf; Azizi, Muhammad Arief; Zariman, Asnazulfadhli (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The Water Level Indicator is beneficial to the public, especially to residents living in rivers. This technology can provide early warnings to residents when the water level is occupying a dangerous level and facilitates workers who control the dam of the river. This technology can alert early through sirens and notifications / messages via smartphones as well as to the river dashboard controllers capable of controlling water gates through their smartphones. The worker who controls the dam of this river no longer needs to go back to the dam's door control house to open the water dam door. Workers who are in charge of controlling dam need to stand in one place only to open their smartphones and control the dam's doorway using the fingertips. To the people living in the river, they do not have to worry about the floods that will happen in their area. They will get an early warning about the flood at any time even when they are sleeping. They will get the warning via notification on their smartphone and siren is places in a certain area to produce a loud noise so that residents can be prepared to face the disaster. It is expect that the Water Level Indicator is able to take a step further and can be use as best as possible and can help the local community.